(untitled) (Journal of Asian Development Studies, 2026)
The study empirically analyses the impact of ICT on socio-economic empowerment of women in South Asian Countries, where women empowerment is measured by secondary school enrollments and economic participation and Independent variable ICT is an index of four variables mobile phones, landline phones, internet users and fixed broadband subscribers. Using panel data set from WDI for the period over 2000-2013 and by applying least square dummy variable model, fixed and random effects models, incorporating efficiency test, Hausman and Breuch Pagan tests, results reveal that ICT has positive and strong significant effect on the female economic participation with the coefficient value of 0.69 in first model. Second model depicts the measure of social aspect, where secondary school enrollment is taken as dependent variable and ICT as independent variable, results of this model also shows that education is highly dependent on ICT with the coefficient value of 1.138. Therefore, in both aspects ICT has positive coefficients values. As a result, we can conclude that overall ICT has positive and significant role for social and economic betterment of females in South Asian region. So, increasing use of these technologies can be even more productive by providing easier access to female education and make sure their economic participation as well.